2005
DOI: 10.1364/ao.44.000126
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for wavelength dependence of the scattering phase function and its implication for modeling radiance transfer in shelf seas

Abstract: More than 90% of stations from the Irish and Celtic Seas are found to have significantly higher back-scattering ratios in the blue (470 nm) than in the red (676 nm) wave band. Attempts to obtain optical closure by use of radiance transfer modeling were least successful for stations at which backscattering ratios are most strongly wavelength dependent. Significantly improved radiance transfer simulation results were obtained with a modified scattering correction algorithm for AC-9 absorption measurements that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
(17 reference statements)
9
22
0
Order By: Relevance
“…Under certain conditions, however, enhancedb bp in blue wavelengths has been measured (McKee and Cunningham, 2005), similar to that found at the whitings station. Conditions that might cause wavelength-dependence would occur when the particle size distribution contains modes of particles and the particle size distribution does not closely follow a Jungian or power-law distribution.…”
Section: Optical Characterization Of Whitingssupporting
confidence: 77%
“…Under certain conditions, however, enhancedb bp in blue wavelengths has been measured (McKee and Cunningham, 2005), similar to that found at the whitings station. Conditions that might cause wavelength-dependence would occur when the particle size distribution contains modes of particles and the particle size distribution does not closely follow a Jungian or power-law distribution.…”
Section: Optical Characterization Of Whitingssupporting
confidence: 77%
“…In contrast, oceanic waters dominated by phytoplankton and covarying byproducts typically range from 0.005 to 0.01 (Twardowski et al, 2001;Boss et al, 2004;Sullivan et al, 2005), while coastal waters with suspended sediments typically do not exceed 0.025 (Twardowski et al, 2001;Boss et al, 2004;Sullivan et al, 2005;McKee et al, 2009;Doxaran et al, 2012). However, values up to 0.05 were observed by McKee and Cunningham (2005) in the Irish and Celtic Seas and values up to 0.036 were observed in the eastern English Channel and southern North Sea (Lubac and Loisel, 2007), in the same range as our measurements from the MB. In our data set, the highest b bp values were associated with stations where cyanobacteria were present.…”
Section: Particle Scattering and Backscatteringsupporting
confidence: 72%
“…The spectra can be attributed to micron-sized aragonite particles. The backscatter variation across the spectra related earlier to wave forcing has been previously observed for whiting events (Dierssen et al 2009, McKee andCunningham, 2005) and has been suggested as resulting from a dominance of a single particle type.…”
Section: Resultssupporting
confidence: 54%